Medical Imaging 2020: Image-Guided Procedures, Robotic Interventions, and Modeling 2020
DOI: 10.1117/12.2549979
|View full text |Cite
|
Sign up to set email alerts
|

CNN-based hierarchical coarse-to-fine segmentation of pelvic CT images for prostate cancer radiotherapy

Abstract: Accurate segmentation of organs-at-risk is important inprostate cancer radiation therapy planning. However, poor soft tissue contrast in CT makes the segmentation task very challenging. We propose a deep convolutional neural network approach to automatically segment the prostate, bladder, and rectum from pelvic CT. A hierarchical coarse-to-fine segmentation strategy is used where the first step generates a coarse segmentation from which an organ-specific region of interest (ROI) localization map is produced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Furthermore, Sultana et al reported that a GAN with a 3D U-net successfully segmented the pelvic region using CT images. 23 The 3D network had the advantage that it obtains more spatial information to use entire image volumes. On the other hand, it has the disadvantage that it requires more training patient data to achieve robust performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sultana et al reported that a GAN with a 3D U-net successfully segmented the pelvic region using CT images. 23 The 3D network had the advantage that it obtains more spatial information to use entire image volumes. On the other hand, it has the disadvantage that it requires more training patient data to achieve robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sultana et al. reported that a GAN with a 3D U‐net successfully segmented the pelvic region using CT images 23 . The 3D network had the advantage that it obtains more spatial information to use entire image volumes.…”
Section: Discussionmentioning
confidence: 99%
“…With 3D volumes, voxel size is rarely isotropic. Liu et al (2019), Wang et al (2019), Sultana et al (2020), andMeyer et al (2021) addressed this issue by resampling to isotropic spacing. Le Cun, Kanter, and Solla (1991) showed that standardisation improves convergence properties by forcing the neurons output to the linear region of the activation functions.…”
Section: Preprocessingmentioning
confidence: 99%
“…Kingma and Ba (2014) mention that Adam is computationally efficient and with low memory requirements, invariant to diagonal rescale of the gradients, highly appropriate for problems with very noisy/or sparse gradients and requires little tuning. Liu et al (2019), Wang et al (2019), Dai et al (2020), Sultana et al (2020), do not mention the optimizer they used, and A. presented a custom one. The remaining articles used Adam with initial learning rates ranging from 1 × 10 −9 to 1 × 10 −2 .…”
Section: Training Parametersmentioning
confidence: 99%
“…A pragmatic next step would be refining the work to label the ROI through a deep learning approach (e.g., UNet, etc.) [ 127 , 189 , 190 , 191 ] and potentially implementing domain adaptation [ 192 ]. Moreover, there would be a greater amount of data available, as not every imaging data set would require biopsy data as well.…”
Section: Next Steps Involving Ai With Radiomicsmentioning
confidence: 99%